2003
DOI: 10.1159/000075120
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phenazine Methosulphate on K<sup>+</sup> Transport in Human red Cells

Abstract: The effect of phenazine methosulphate (PMS; 1 mM) on (86Rb+) K+ transport in human red cells was investigated to ascertain its action on the K+-Cl- cotransporter (KCC; defined as the Cl- dependent component of K+ flux measured in the presence of ouabain and bumetanide) and the Ca2+-activated K+ channel (Gardos channel; defined as the clotrimazole, 5 µM, -sensitive K+ flux). In the presence of Ca2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…XO/HO mixtures generate SOA and hydrogen peroxide extracellularly (Baskurt et al , 1998; Rogers et al , 2009), whilst PMS generates SOA intracellularly (Nishikimi et al , 1972; Maridonneau et al , 1983); NO 2 oxidises Hb to metHb (Muzyamba et al , 2000); t BHP increases generation of peroxyl and alkoxyl free radicals (Davies, 1989); whilst HOCl produced by myeloperoxidase released from neutorphils may also oxidise membrane thiols (Vissers et al , 1994; Gorudko et al , 2016). Red cell PS exposure is most reliably stimulated by elevation of intracellular Ca 2+ (Bevers & Williamson, 2010) whilst a number of oxidants have previously been shown to increase red cell cation permeability (Gibson & Muzyamba, 2003a,2003b). We therefore hypothesised that oxidants may act synergistically with intracellular Ca 2+ to increase PS exposure and alter its Ca 2+ affinity, thereby accounting for the raised percentage of PS‐positive red cells in SCA patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…XO/HO mixtures generate SOA and hydrogen peroxide extracellularly (Baskurt et al , 1998; Rogers et al , 2009), whilst PMS generates SOA intracellularly (Nishikimi et al , 1972; Maridonneau et al , 1983); NO 2 oxidises Hb to metHb (Muzyamba et al , 2000); t BHP increases generation of peroxyl and alkoxyl free radicals (Davies, 1989); whilst HOCl produced by myeloperoxidase released from neutorphils may also oxidise membrane thiols (Vissers et al , 1994; Gorudko et al , 2016). Red cell PS exposure is most reliably stimulated by elevation of intracellular Ca 2+ (Bevers & Williamson, 2010) whilst a number of oxidants have previously been shown to increase red cell cation permeability (Gibson & Muzyamba, 2003a,2003b). We therefore hypothesised that oxidants may act synergistically with intracellular Ca 2+ to increase PS exposure and alter its Ca 2+ affinity, thereby accounting for the raised percentage of PS‐positive red cells in SCA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative damage has also been associated with deleterious effects on red cell cation balance. It causes inhibition of the plasma membrane Ca 2+ pump (Shalev et al , 1981; Zaidi et al , 2003), which maintains intracellular Ca 2+ concentrations at low levels, perhaps via interaction with calmodulin (Gao et al , 2001), and also has marked effects on red cell potassium permeability (Gibson & Muzyamba, 2003a,2003b). A randomized controlled trial has also recently shown that l ‐glutamine, believed to act predominantly as an antioxidant, reduced the frequency of acute pain in SCA (Niihara et al , 2016).…”
mentioning
confidence: 99%
“…Other studies have also implicated that ROS are involved in the regulation of KCC activity in red blood cells (Muzyamba et al, 2000;Gibson et al, 2003). NEM appeared to generate ROS by activation of the NADPH oxidase which is known to exist in HepG2 cells (Ehleben et al, 1997;Cool et al, 1998).…”
Section: Discussionmentioning
confidence: 90%
“…A number of oxidants including nitrite (Muzyamba et al. ), phenazine methosulfate (Gibson and Muzyamba ,b), 1‐chloro‐2,4‐dinitrobenzene (Gibson and Muzyamba ,b), and peroxynitrite (Kucherenko et al. ) have previously been found to have significant stimulatory effects on K + transport systems in red cells from normal individuals and from other species, and may therefore mediate solute loss and red cell dehydration.…”
Section: Introductionmentioning
confidence: 99%